Collaborative Art Performance “Melumat-Limit” - Soerio, Anggieta Maharani; Dana, I Wayan; Agustina, Arinta (TUMATA: Journal of Cultural and Arts Management, 2024)
The Art Collaboration Performance "Melumat Limit" is an art platform that collaborates more than one branch of art that is realized into a performance. "Melumat Limit" is interpreted as fighting and defeating existing boundaries but not completely eliminating them. This creation explains the steps of managing a performance, especially the Art Collaboration Performance "Melumat Limit". The method used by the author in the creation of the Performing Arts Collaboration "Melumat Limit" is qualitative with an approach to event management, contemporary dramaturgy and aesthetics. This creation aims to provide an alternative space for artists and audiences in organizing a performance, as a way of articulating art, and as a reference for learning about the process of creating an art collaboration performance. A performance art creation is briefly divided into three stages, namely pre-production, production or technical management, and post-production. Many stages are carried out to realize an art collaboration performance. Knowledge of equipment is also something that must be considered, considering the various types of equipment that must be in accordance with the needs.